The effect of corporate governance and firm characteristics on earnings management practice among Nigerian companies - Miko, Nuraddeen Usman (2016)
Earnings management has become an avenue for the managers to report determined corporate performance which later led to the collapse of the corporations. Corporate governance mechanisms instituted to control the managers’ opportunistic action which reduces agency cost of the firms. The present study investigates the relationship between the board of directors, audit committee and firm characteristics and earnings management practice in Nigerian listed companies. The study also investigates the earnings management practice in the pre- and post-Corporate Governance Code 2011 periods. The study argues that interaction of institutional ownership between audit committee and earnings management practice mitigates opportunistic behaviors of managers. The study measured the effectiveness of the revised Nigerian Corporate Governance Code 2011 mechanisms which came into effect in 2011. Data were gathered from 405 non-financial company-year observations drawn from the population of Nigerian listed companies for the period of 2009-2013. With reference to the agency theory, political cost theory and ethical theory, the present study finds that the revised Corporate Governance Code 2011 has a significant effect in reducing the level of earnings management practice in the post Corporate Governance Code 2011 period; corporate governance mechanisms significantly reduce earnings management practice; and institutional ownership interaction effect in the audit committee is significantly more active in reducing earnings management. Based on the findings, the study suggests that for future policy effective corporate governance is required to mitigate earnings management activities. The regulators need to encourage participation of institutional ownership in the board of public listed companies.